2008
DOI: 10.1155/2008/202179
|View full text |Cite
|
Sign up to set email alerts
|

Time‐Frequency Characterization of Rotating Instabilities in a Centrifugal Pump with a Vaned Diffuser

Abstract: This paper presents acoustic and flowdynamic investigations of large-scale instabilities in a radial pump with a vaned diffuser. Pressure fluctuations were measured with transducers placed flush at the inlet duct, at the impeller discharge, and in the vane diffuser walls. Two impeller rotation speeds were analyzed in the study, at design, and at off-design flow rates. A spectral analysis was carried out on the pressure signals in frequency and in time-frequency domains to identified precursors, inception, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…In a similar way, Bousquet et al [11] found that 6 vortices are formed and shed per revolution in their centrifugal compressor, thus being responsible of a observed tone at six times compressor rotational frequency. Besides, Pavesi et al [38] attributed a tone corresponding to 66% of impeller rotation to a sequence of vortices in the wake region originated at blade midchord in a centrifugal pump with vaned diffuser. Figure 11 corresponds to 77 g/s operating conditions.…”
Section: Flow Field Investigationmentioning
confidence: 99%
“…In a similar way, Bousquet et al [11] found that 6 vortices are formed and shed per revolution in their centrifugal compressor, thus being responsible of a observed tone at six times compressor rotational frequency. Besides, Pavesi et al [38] attributed a tone corresponding to 66% of impeller rotation to a sequence of vortices in the wake region originated at blade midchord in a centrifugal pump with vaned diffuser. Figure 11 corresponds to 77 g/s operating conditions.…”
Section: Flow Field Investigationmentioning
confidence: 99%
“…Yao [29] analysed the unsteady structure of the pressure fluctuation by using many methods, including wavelet transform, short-time Fourier transform. Pavesi et al [30] performed a spectral analysis of the pressure fluctuation signal and applied the wavelet analysis method to evaluate the pressure fluctuations transient characteristics. Previous studies [31,32] have also used wavelet correlation to analyse the unique capability for decomposing the correlation of arbitrary signals.…”
Section: Continuous Wavelet Transformmentioning
confidence: 99%
“…The flow field into the wickets gates channel starts to manifest a full three-dimensional flow structure. These disturbances, related to the boundary layer separation and stall, were noticed with images of the amplitude at a frequency very close to the impeller frequency St = 0.143 and to the sub-tonal frequency St « 0.335 identified by experimental measurements [24][25][26] also in steady conditions. With a further reduction of the impeller speed, the rotating partial stall rules the interactions.…”
Section: Numerical Analysis Of the Pump-turbine In A Power Reduction mentioning
confidence: 99%